Back to basics: definitions and processes of assessments (Praxis Educativa, 2010)
In a performance – and results – driven educational world the concept of formative assessment has inspired the educational community by its discourse and focus on learning and learners. However, a number of controversies have surfaced: primary among these are terminological opacities and disparities both within and across continents and sectors (TARAS 2007b, 2009). Among others, Perrenoud (1998) signals the importance of positioning theoretical and practical discourse on assessment within a wider pedagogic context and within theories of learning. Taras (2005) argues that concepts of assessment, including formative assessment, are best and more effectively understood firstly within the wider assessment framework and, secondly, within the relationships of summative, formative and self-assessment. This paper examines definitions of assessments. It begins with basic concepts of assessment, summative, formative, self-assessment and feedback and inter-relates these. The principles inherent in definitions set the parameters of both processes and practice as part of a logical sequence and framework. Keywords:Assessment. Formative assessment. Summative assessment.